Hubungan Dukungan Suami dan Dukungan Keluarga denganKeaktifan Mengikuti Senam Hamil - Hadijah Hadijah; Risna Yunita Asmin; Rahmiyani Saad; Nurmiati; St Aminah Ali (Window of Midwifery Journal, 2026)
The activity of pregnant women in participating in pregnancy exercises regularly is influenced by family involvement from the beginning of pregnancy. Family support helps mothers cope with various physical and emotional changes during pregnancy. Therefore, at least one pregnancy exercise meeting accompanied by family is recommended. The role of the family is very important, because pregnant women who receive attention and support tend to experience fewer emotional and physical disorders, adapt more easily, and have a lower risk of labor complications. This study is a quantitative study using a cross-sectional approach, where researchers sought the relationship between husband's support and family support with the activity of participating in pregnancy exercises at the Tamalanrea Jaya Community Health Center. The study population was all pregnant women in the second-third trimester at the Tamalanrea Jaya Community Health Center, totaling 35 pregnant women with a total sampling technique. Based on the results of the chi-square test, there is a relationship between husband's support (p-value = 0,008 <α = 0,05) and family support (p-value = 0,018 <α = 0,05) with the activity of participating in pregnancy exercises at the UPT Tamalanrea Jaya Community Health Center